Increasing oxygen uptake in cross-country skiers by speed variation in work intervals - Rønnestad, B. R.; Bakken, T. R.; Thyli, V.; Hansen, J.; Ellefsen, S.; Hammarstrøm, D. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Accumulated time at a high percentage of peak oxygen consumption (VO2peak) is important for improving performance in endurance athletes. The present study compared the acute physiological and perceived effects of performing high-intensity intervals with roller ski double poling containing work intervals with (1) fast start followed by decreasing speed (DEC), (2) systematic variation in exercise intensity (VAR), and (3) constant speed (CON).